2021
DOI: 10.1111/opo.12863
|View full text |Cite
|
Sign up to set email alerts
|

Objective changes in astigmatism during accommodation

Abstract: Purpose Previous studies have shown small but clinically significant changes in the power and axis of astigmatism when the eye accommodates. Monocular objective measurements of the eye during accommodation, when the object approaches the eye without convergence, also reveal small astigmatic changes. Moreover, it is known that the eye exhibits ocular cyclotorsion at different gaze angles. Since accommodation and convergence normally occur simultaneously, we studied the change in the magnitude and axis of astigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(81 reference statements)
0
7
0
Order By: Relevance
“… 12 In agreement with these findings, other authors found no differences in terms of J0 and J45 between other instruments to conduct automated subjective refraction and the traditional subjective refraction as the gold standard, also presenting similar 95% limits of agreement. 8 , 13 A recent study by Lara-Lacárcel et al 28 described how instrumental accommodation could induce changes in astigmatism power and its axis. They reported mean changes in J0 by about −0.02 D per dioptre of accommodation and minimal changes in J45.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In agreement with these findings, other authors found no differences in terms of J0 and J45 between other instruments to conduct automated subjective refraction and the traditional subjective refraction as the gold standard, also presenting similar 95% limits of agreement. 8 , 13 A recent study by Lara-Lacárcel et al 28 described how instrumental accommodation could induce changes in astigmatism power and its axis. They reported mean changes in J0 by about −0.02 D per dioptre of accommodation and minimal changes in J45.…”
Section: Discussionmentioning
confidence: 99%
“…Another source of variability could be due to the required conversion from refractive measurement in spherical equivalent to vertical meridian for the present WAM-5500A data using additional, static autorefractor measurements (see Data Processing). The conversion method assumed that cylinder power and axis collected during static WAM-5500A measurements remained constant for dynamic recording (see Equations 1 and 2 ), 50 and static measures were collected at each tested accommodative demand to determine cylinder power and axis with greater accuracy. Aldaba et al (2015) did not report how conversions were applied (comparisons were conducted using spherical equivalent), but it nevertheless raises the possibility that the present conversion approach may have introduced additional variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in astigmatism due to accommodation have been shown to be clinically relevant for large accommodative demands exceeding 4.00 DS. 34 Future investigations should compare these outcomes in participants without the ability to accommodate by use of cycloplegic agents and compare between cohorts of similar age distributions.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%